The Impact of the Companions' Approach on Ensuring the Quality of Thought among Muslims: Musannaf Ibn Abi Shaybah as a Model - Al-Hammami, Taleb Ibn Ahmad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
The study aims to explain the Companions' approach to achieving intellectual security and the quality of sound thought. Also, it clarifies the error of extremists and their violation of the Companions' approach. The study followed the inductive, deductive, and descriptive approaches to achieve the study objective. The study concluded that the Companions' approach is a true benchmark by which the moderation or deviation of thought is measured. Also, the greatest immunization of thought deviation is to adhere to the Book and the Sunnah according to the Companions' understanding. This study is distinguished from previous studies in that it collected the impact of the Companions from Musannaf Ibn Abi Shaybah in achieving intellectual security. It set standards for the quality of thought among the Companions to serve as a beacon for scholars and preachers in protecting Muslim societies from thought deviations and refuting misleading suspicions to preserve the integrity of future generations and their ideas.